Long-term follow-up of patients with chronic total coronary artery occlusion previously randomized to treatment with optimal drug therapy or percutaneous revascularization of chronic total occlusion (COMET-CTO) - Juricic, Stefan A.; Stojkovic, Sinisa M.; Galassi, Alfredo R.; Stankovic, Goran R.; Orlic, Dejan N.; Vukcevic, Vladan D.; Milasinovic, Dejan G.; Aleksandric, Srdjan B.; Tomasevic, Miloje V.; Dobric, Milan R.; Nedeljkovic, Milan A.; Beleslin, Branko D.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The COMET-CTO trial was randomized prospective study to assess long term follow-up in patients with chronic total occlusion (CTO) in coronary artery treated either with percutaneous coronary intervention (PCI) of CTO or with optimal medical therapy (OMT). During the 9 months follow-up the incidence of major adverse cardiac events (MACE) did not differ between two groups, with no death and myocardial infarction (MI). Now we report a real long-term follow-up result (56 ± 12 months) Methods: Between October 2015 and May 2017 a total of 100 patients with CTO were randomized into two groups of 50 patients: PCI CTO or OMT group. The primary end point of the current study was the incidence of MACE defined as: cardiac death, MI and revascularization (PCI or coronary artery bypass graft (CABG)). As secondary exploratory outcomes, we analysed all cause-mortality. Results: Out of 100 randomized patients, 92 were available for a long-term follow-up (44 in PCI and 48 in OMT group). The incidence of MACE did not differ significantly between the two groups (p=0.363). Individual components of MACE were distributed as follows: cardiac death (OMT vs PCI group, 6 vs 3, p=0.489), MI (OMT vs PCI group, 1 vs 0, p= 1) and revascularization (PCI: OMT vs PCI group, 2 vs 2, p=1; CABG: OMT vs PCI group, 1 vs 1, p=1). There was no significant difference between two group regarding individual component of MACE. Six patient died from non-cardiac causes (5 deaths in OMT and 1 death in the PCI group (p=0.206)). Kaplan- Meier survival curves for MACE did not differ significantly between the study groups (log-rank 0.804, p = 0.370). Regarding secondary exploratory outcome, all together 15 patients died at 56 ± 12 months (11 in the OMT and 4 in the PCI group) (p = 0,093). Kaplan-Meier survival curves for all-cause mortality did not differ significantly between the two groups (log rank 3.404, p = 0.065). Conclusion: The incidence of MACE did not differ significantly between PCI and OMT groups. There was a trend towards a statistically significant difference in all-cause mortality in favour of patients treated with PCI.